Harnessing Sustainable Water Management through Innovation and Efficiency at ESPOCH - Córdova, Rafael; Vanegas, Pablo; Vaca, Byron (Universitas Diponegoro, 2023)
ESPOCH, an Ecuadorian university with a unique underground water source, is developing a drinking water plant to serve its population of over 22,000 students and staff members. The paper explores innovative measures and technology for efficient water utilization at ESPOCH, including a secondary, untreated water line for non-potable uses and the adoption of smart water management technologies to monitor and regulate water consumption. This approach addresses the provision of safe drinking water, plastic waste reduction, and health risks linked to poor water quality. ESPOCH's innovative water management approach contributes to the broader discussion on sustainable universities' role in managing water resources. The study highlights the importance of technology and innovation in resource conservation and utilization in higher education institutions, with ESPOCH serving as a valuable example for other universities addressing water scarcity, environmental impact, and promoting sustainable practices.